Potential sources of groundwater pollution and a proposal for prioritizing inspection areas in an industrialized municipality - de Jesus, Lucas Scarpanti [UNESP]; Riyis, Marcos Tanaka [UNESP]; Giacheti, Heraldo Luiz [UNESP] (Lepidus Tecnologia, 2021)
This paper presents a methodology for selecting areas with potential sources of groundwater pollution and its application in an industrialized municipality in the interior of São Paulo. As there are multiple potential sources of pollution and difficulty in establishing criteria for prioritizing areas to be investigated, it is necessary to use tools and techniques that make it possible to guide and plan in situ site inspections. The data from CETESB's registry of pollution source activities was used applying the POSH-IG method associated with Kernel density spatial analysis in a Geographic Information System. The findings revealed a hot spot of 6.96 km² with 383 industries with high groundwater pollution potential; within it the highest range of Kernel density presents 124 industries occupying an area of 0.41 km. A major difference between the number of contaminated sites registered by CETESB (two) and the quantity (383) of sources with high pollution potential (POSH-IG index equal to 3) was observed at that hotspot area. Therefore, the applied methodology was satisfactory in indicating areas of interest for field inspections, identifying 6.96 km² area in a 450.38 km² municipality, which has a high polluting potential for groundwater and only two known contaminated areas. This approach can be used to guide the inspection of sites that could contaminate groundwater.
Fontes potenciais de poluição das águas subterrâneas e uma proposta de priorização de áreas de fiscalização em um município industrializado
Keywords: GIS; Groundwater; Kernel density; Polluting potential; POSH-IG